BEGINNINGS OF SERBIAN SOKOLISM IN AMERICA (Fiep Bulletin - online, 2016)
Serbs in America in the early 1909 began to accept the idea of Serbian Sokolism as a way of gathering and exercising in the manner of spiritual and body strengthening and rising of their nation. In the mid 1909 began forming of first Serbian Sokol societies, and by the end of that year there were two already formed. Besides Serbs, other Slavic nations: Czechs, Slovaks, Croats, Russians and others also began with forming of their own Sokol societies. First Serbian Sokol Society in America was formed in May 1909 in Cincinnati (Ohio). We researched its work until May 1914 (founding, beginning, acceptance in SSSA, participation in the First Serbian Sokol Slet in America in 1912, participation in the manifestations of other Serbian societies and organizations, as also participation in happenings (events) of other Slavic nations and societies). During writing we used historical methodology. Primary and secondary historical sources originated in the time of founding and work of Society until May 1914, as also the ones originated later, were reviewed and critically analyzed.
Keywords: Sokols; Union; Slet.